2017
DOI: 10.1038/sj.bdj.2017.361
|View full text |Cite
|
Sign up to set email alerts
|

The oral health of individuals with dental phobia: a multivariate analysis of the Adult Dental Health Survey, 2009

Abstract: Background: Adults with dental phobia have been reported to have poorer oral health and oral health related quality of life. The aim of this study is to explore the social and demographic correlates of oral health and oral health related quality of life (OH-QoL) of people with dental phobia compared to the non-phobic population in the United Kingdom using the data from Results: People with dental phobia are more likely to have one or more decayed (caries) teeth/missing teeth. Furthermore, their self-reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…16,17 In addition, some people fear the diagnosis and treatment of periodontal diseases (dental phobia) and are negligent with regard to prevention, maintenance and early detection. 18 Therefore, the actions of individuals are governed by the personal misconceptions about their dental needs. An individual´s perception of control is regarded as an important socio-behavioral factor in general.…”
Section: Evidence For the Population (Individual-level Measures)mentioning
confidence: 99%
“…16,17 In addition, some people fear the diagnosis and treatment of periodontal diseases (dental phobia) and are negligent with regard to prevention, maintenance and early detection. 18 Therefore, the actions of individuals are governed by the personal misconceptions about their dental needs. An individual´s perception of control is regarded as an important socio-behavioral factor in general.…”
Section: Evidence For the Population (Individual-level Measures)mentioning
confidence: 99%
“…A longitudinal study among the Gullah African Americans also showed that uncontrolled T2DM relates to a nearly two times higher magnitude of periodontal tissue destruction compared to their counterparts (controlled diabetics and non-diabetics) [24]. The results are further substantiated by other investigations from the United Kingdom [25], United States of America [26], India [27], and Spain [28]. A systematic review and meta-regression of longitudinal studies also con rms this association.…”
Section: Discussionmentioning
confidence: 63%
“…It happens that patients do not attend another appointment after the diagnosis has been made. Reasons for this are, for example, a removal or even fear of treatment [52].…”
Section: Discussionmentioning
confidence: 99%